PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA MEREK ROKOK DJI SAM SOE (Students' Journal of Economic and Management, 2014)
This research is a study that tested the effect of product quality, brand image, and price on customer satisfaction. Samples taken is the consumer of cigarettes in the District of Semarang Candisari as many as 100 respondents. The data obtained through primary data by distributing questionnaires and filled in accordance with the actual situation by the consumer of cigarettes in the District Candisari Semarang. Data taken at random with a random sampling method or sampling method with certain considerations, and analyzed using linear regression. The results of the study by SPSS showed that the variable quality of the product (XI) effect on customer satisfaction (Y). This is evidenced by the much greater than t table t which is equal to: 3.348 t> t table 1.984 and has a significant level of 0.000 <0.05 thus Ho is rejected and Ha1 accepted, meaning that product quality is variable positive and significant effect on customer satisfaction. Brand image variable (X2) effect on customer satisfaction (Y). This is evidenced by the much greater than t table t which is equal to: 2,727 t> t table 1.984 and has a significant level of 0.000 <0.05 so that Ho refused and Ha2 accepted, meaning that the brand image is variable positive and significant effect on customer satisfaction. While the price variable (X3) had no effect on customer satisfaction (Y). This is evidenced by his more than t table t which is equal to: 0.651 t <t table 1.984 and has a significant level of 0.000 <0.05 thus Ho is accepted and Ha3 rejected, meaning that the price variable is negative and significant effect oncustomer satisfaction.Keywords: Quality Product, Brand image, price, and customer satisfaction